2017
DOI: 10.1590/s1677-5538.ibju.2016.0324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Spies™ modalities image quality

Abstract: Introduction The Spies™ system (Karl-Storz®) was introduced into digital ureteroscopy to improve endoscopic vision. To date, there is no data to either indicate which of the Spies modalities is better for improving diagnosis and treatment procedures, nor to compare the modalities in terms of image quality. The aim of this study was to evaluate and compare the image quality of five Spies™ modalities (SM) to the standard white light in an in-vitro model.Materials and Methods Two standardized grids and 3 stones o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Kamphuis et al [15] compared the performance of C&CH with that of WL cystoscopy, investigating 80 bladder tumors, and concluded that C&CH and Spectra B offered the best tumor visualization. Emiliani et al [16] used standardized templates to assess image quality with regard to color contrast and image definition of Flex XC (Karl Storz, Tüttlingen, Germany). Clara and C&CH scored better than WL ( p = 0.0139 and p < 0.05, respectively), but Spectra A and Spectra B scored worse than WL ( p = 0.0005 and p = 0.0023).…”
Section: Diagnostic Workupmentioning
confidence: 99%
“…Kamphuis et al [15] compared the performance of C&CH with that of WL cystoscopy, investigating 80 bladder tumors, and concluded that C&CH and Spectra B offered the best tumor visualization. Emiliani et al [16] used standardized templates to assess image quality with regard to color contrast and image definition of Flex XC (Karl Storz, Tüttlingen, Germany). Clara and C&CH scored better than WL ( p = 0.0139 and p < 0.05, respectively), but Spectra A and Spectra B scored worse than WL ( p = 0.0005 and p = 0.0023).…”
Section: Diagnostic Workupmentioning
confidence: 99%
“…Virtual chromoendoscopy (VCE) augments and detects the spatial variance in light absorption and the scattering properties of tissue and organs in diagnosis and therapy, improving the contrast between abnormal and healthy tissue. According to the illumination light and image processing methods used, VCE can be categorized into three groups: (i) pre-processing VCE (e.g., NBI [31] and blue-light imaging (BLI) [32]), which uses a modified spectrum of light that coincides with the central peak of the absorption characteristics of haemoglobin in the blood vessels, enhancing the contrast between capillaries and adjacent tissue from the mucosa and submucosa; (ii) post-processing VCE (e.g., FICE, i-scan and the Storz professional image enhancement system (SPIES) [33]), which processes digital images to achieve a similar effect as pre-processing VCE via spectral reconstruction algorithms; and (iii) linked colour imaging (LCI) [34] and i-scan optical enhancement (i-scan OE [35]), which incorporate both pre-and post-processing methods.…”
Section: ) Virtual Chromoendoscopymentioning
confidence: 99%
“…Among these modes, Clara provides homogeneous illumination with clear visibility of darker regions due to the adaptation of local brightness, while Chroma increases the contrast of the images to enhance the structures within the displayed image. The rest of the modes are SPECTRA A and SPECTRA B, which shift and exchange the image effective spectral response, highlighting the contrast between different tissues and structures [ 44 ] related to different penetration depths [ 46 ] ( Figure 10 ). All these five modes are potential candidates to choose the best option according to the specific clinical situation.…”
Section: Optical Imaging Technologies In Major Hospital Departmentmentioning
confidence: 99%